Evaluation of the Effects of Core-Quick Strength and Core-Plyometric Studies on Balance, Agility and Strength Traits of Volleyball Players - DEVRİM, Uğur and ERDEM, Kâmil (Asian Journal of Education and Training, 2019)
The aim of this study is to investigate the effects and differences of two different strength training models on balance, agility and strength traits of volleyball players. 45 female athletes aged 12.08 ± 0.82 who played volleyball in a private club participated in the study. The athletes who participated in the study were divided into three groups as core-plyometric (KRP) (n=15), core-quick strength (KRC) (n=15) and control (KNL) (n=15) groups. Within the scope of the study, KRP group performed plyometric training after core training and KRC group performed quick strength training after core training. The KNL group continued their volleyball training The trainings were conducted 2 days a week for 8 weeks. Height, weight, BMI, t-test, standing long jump test, flamingo balance test and throw-in test were applied to all three groups before and after the study. The data obtained in the pre and post test were evaluated with a statistics package program and the significance level was determined as p<0.05. The One-Way ANOVA test and Paired-Samples t-test were used for statistical analysis. As a result, a significant difference was found in the standing long jump test in all three groups (p <0.05). Throw-in and flamingo balance tests showed a significant difference in the KRP and KRC groups (p<0,01), but not in the KNL group (p>0,05). T-test showed significant difference in KRP and KRC groups (p<0.05), but no significant difference was found in KNL group (p>0,05). When the differences between the groups were examined,no significant differences were found between the averages as a result of height, standing long jump, throw-in and flamingo balance tests (p>0.05),and the KRC group showed significantly more improvement than the KNL group in the t-test.